OTENTITAS HADIS DALAM PERSPEKTIF HARALD MOTZKI - M. Rofiq Junaidi (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2015)
To study Hadis, authenticity, validity, and reliability of themethod are very fundamental dimension. The doubt of some of theMuslim scholars on the role of Hadis as second aurthorized sourceafter Qur‟an were not fully related to their resistances to Sunnah, butmore on the doubt to the accuracy of method which is used to decidethe originality of Hadis. The study on the authetification of Hadiswhich is done by Harald Moztki started from the data analysis on thebook of al-Musannaf written by Abdurrazzaq As-Shan‟ani. According toMoztki, the book of al-Musannaf is documentation of Hadis which isvery authentic since 1st Century of Hijriyah. It meant there was realevidence that Islamic Lawa has exis at the time. This finding directlybrought down Moztki predecessor, G.H.A. Juynboll J. and projectingback of Schacht that stated that Sanad‟s system started from the 2ndcentury of Hiriyah.